Pengembangan Ekowisata Berkelanjutan Di Wisata Gunung Jae, Desa Sedau Kecamatan Narmada, Kabupaten Lombok Barat - Alifiyan Rizki Naufal Muhayadi; Baiq Silvana Rahmawati; Karina Rahim; Isnaeni Isnaeni; Ika Wijayanti (Student Research Journal, 2024)
This study discusses how a sustainable ecotourism development strategy in Gunung Jae Tourism, Sedau Village, Narmada District, West Lombok Regency. The problem in this study is about the development of Gunung Jae Tourism in Sedau Narmada Village which has an impact on the residents there how to take advantage of the presence of this Gunung Jae Tourism. The purpose of this research is to find out how the sustainable ecotourism development strategy in Gunung Jae Tourism, Sedau Village, Narmada. The theory used in this research is Social Capital Theory. The method in this research is descriptive qualitative, with data collection techniques using observation, interviews, and documentation. The technique of determining informants uses purposive sampling and snowball sampling. The result of this study is the development of ecotourism on Mount Jae which has been carried out by the tourism manager has succeeded in increasing the income of the community in Sedau village, so that it can be one of the factors tha Gunung Jae tourism can be developed sustainably.